REVITALISASI LAJNAH BAHTSUL MASAIL DALAM MENINGKATKAN PEMIKIRAN KRITIS SANTRI DI PONDOK PESANTREN ZAINUL HASAN GENGGONG PROBOLINGGO - Rohilatusalamah; Irzak Yuliardy Nugroho; Saiful Islam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the revitalization process of Lajnah Bahtsul Masail (LBM) and its contribution to improving the critical thinking skills of students at Zainul Hasan Genggong Islamic Boarding School Probolinggo, particularly the female students’ boarding section. This research employs a qualitative approach with a case study design. Data collection techniques include observation, interviews, and documentation, involving key informants such as LBM administrators, supervising teachers, and active students. The results of the study indicate that the revitalization of LBM was carried out through restructuring the organizational system, reorganizing activity schedules, strengthening the discussion (musyawarah) methods, and increasing student participation. This revitalization has a positive impact on enhancing students’ critical thinking skills, as reflected in their ability to analyze problems, construct arguments, and formulate conclusions systematically. Thus, LBM functions as a strategic forum in developing students’ critical reasoning within the Islamic boarding school environment.